Educação Física que não escolhe, acolhe: pedagogia engajada para a diversidade - Branquinho, Paola Amorim (Universidade Federal de São Carlos, 2025)
The school environment should be a space of plurality and diversity, reflecting the multiple experiences of individuals, however some groups still face major challenges, including intolerance, discrimination and prejudice. Physical Education, historically, has segregated many people, whether for physical reasons, gender, ethnicity, mobility, among others, excluding them from its practice for wanting healthy and strong bodies. However, just like the historical context, Physical Education has also been changing with a view to adapting to this change, which today requires including "everyone" in its practices. Over the last few decades it has begun to undergo transformations, as it has become a more welcoming and inclusive space. Diversity is a topic that has been the subject of study and debate in a variety of academic contexts, including the area of Physical Education. The present research aims to analyze the educational processes emerging from a teaching unit aimed at welcoming diversity in Physical Education classes for a class of 8th grade students. This is a qualitative research of the action research type demarcated by the implementation of a didactic unit composed of 24 classes, where actions were developed such as: readings, research, video analysis, conversation circles, game experiences and debates around this theme.The data production instrument used was the class diary, with participant observation and audio recordings as sources. The research data was analyzed by analyzing coding categories in three stages: organization and reading of documents, coding of materials and categorization. The results and their analysis are organized into a descriptive category referring to the report on the preparation of the didactic unit and its presentation and three other analytical categories.The first, “Interrelationship between teaching and learning”. The second “Breaking walls and building bridges”, and the third, “Our history, our perspective, our community”. The experience of the proposed themes contributed to a critical awareness among students about inequalities in bodily practices. In view of the above, the construction of a didactic unit aimed at embracing diversity based on Dialogical Education and Engaged Pedagogy can be seen as a great pedagogical instrument in Physical Education classes. Thus, it can be concluded that dialogue, practical experiences, problematizations, and welcoming pedagogical practices can contribute to minimizing inequalities and to the understanding that bodily practices need to be recognized as a right for all bodies.
Physical Education that does not choose, welcomes: challenges and possibilities for a diverse and dialogic pedagogical practice.
Keywords: Educação física escolar; Diversidade; Práticas pedagógicas; Dialogicidade; Pedagogia engajada; School physical education; Diversity; Pedagogical practices; Dialogicity; Engaged pedagogy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM